Government Size and Business Cycle Volatility; How Important Are Credit Constraints? - Markus Leibrecht; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
In this paper we analyze how the availability of credit influences the relationship between government size as a proxy for fiscal stabilization policy and the amplitude of business cycle fluctuations in a sample of advanced OECD countries. Interpreting relatively low loan-tovalue ratios as an indication for tight credit constraints, we find that government size exerts a stabilizing effect on output and consumption growth fluctuations only when credit constraints are relatively tight. Our results are robust with respect to different measures of government size and provide support for the hypothesis that credit market frictions play a crucial role in the transmission of fiscal policy.
Keywords: E62; E32; 330; business cycle; volatility; fiscal policy; stabilization policy